Toxicidade tópica de extratos da Rutaceae esenbeckia pumila em operárias de formigas-cortadeiras Atta laevigata e Acromyrmex balzani - (:unkn) unknown (Universidade Estadual de Goiás, 2017)
The indiscriminate use of synthetic chemical pesticides along with the peculiar difficulties of developing formicidal formulations of delayed effect to control leaf-cutting ants have encouraged the search for alternative products. Thus, in this work, the toxicity of plant extracts of Esenbeckia pumila, Rutaceae,was evaluated for leaf-cutter ant (Atta laevigata and Acromyrmex balzani). Ethanolic extract of leaves and fruits of E. pumila were fractionated, using solvents in increasing order of polarity. This process was carried out using vacuum filtration after incorporation of the microcrystalline cellulose D adjuvant to the ethanolic extract. Five leaf fractions were obtained: E. pumila (EPFEH); E. colum (EPFE); E. pumila dichloromethane extract (EPFED); E. pumilaethyl acetate extract (EPFEA); E. pumila methanolic extract (EPFEM); and E. pumila ethanolic fruits extract (EPFrE). These fractions, in different concentrations, were applied topically to A. laevigata and A. balzani workers. The toxicity (worker mortality) as due to the dose of the fractions of E. pumila were estimated by Probitmodel. Also, the mortality rate was plotted over time after exposing the workers to these extracts. All the extracts fractions of the tested plant showed a formicidal effect when compared to the control, without application of the plant extract. All fractions of the tested extracts showed to be more toxic to the herbal A. laevigata, when compared to the others A. balzani. A small proportion of workers was dead in the first hours after application of the extracts when compared to the dead workers after longer exposure of the extracts suggest delayed effect of all the extracts of E. pumila.
Keywords: Planta inseticida; Attini; Mortalidade; Insecticide; Attini; Mortality; CIENCIAS AGRARIAS